The effect of social networks on migrants' labor market integration: A natural experiment - Klarita Gërxhani; Yuliya Kosyakova (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
Empirically identifying the causal effect of social networks on migrants' economic prospects is a challenging task due to the non-random residential sorting of migrants into locations with greater opportunities for (previous) connections. Our study addresses this selection-bias issue by using a unique natural-experimental dataset of refugees and other migrants that were exogenously allocated to their first place of residence by German authorities. The empirical results reveal a positive causal effect of social networks on migrants' transition rate to the first job, but only if the networks are mobilized for the job search. – – Die empirische Identifikation des kausalen Effekts sozialer Netzwerke auf die wirtschaftliche Integration von Migranten ist eine herausfordernde Aufgabe, da Migranten sich nicht zufällig nach (Wohn-)Orten mit größeren Möglichkeiten für (frühere) Verbindungen sortieren. Unsere Studie adressiert dieses Problem der Selektionstendenz, indem sie einen einzigartigen natürlich-experimentellen Datensatz von Flüchtlingen und anderen Migranten verwendet, die von deutschen Behörden exogen ihrem ersten Wohnort zugewiesen wurden. Die empirischen Ergebnisse zeigen einen positiven kausalen Effekt sozialer Netzwerke auf die Übergangsrate von Migranten zum ersten Job, jedoch nur, wenn die Netzwerke für die Arbeitssuche mobilisiert werden.
Keywords: F22; L14; J61; R23; 330; first-generation migrants; labor market; natural experiment; network social capital; refugees